Social Preference Deficits in Juvenile Zebrafish Induced by Early Chronic Exposure to Sodium Valproate - Liu, Xiuyun; Zhang, Yinglan; Lin, Jia; Xia, Qiaoxi; Guo, Ning; Li, Qiang (Frontiers in Behavioral Neuroscience, 2016)
Prenatal exposure to sodium valproate (VPA), a widely used anti-epileptic drug, is related to a series of dysfunctions, such as deficits in language and communication. Clinical and animal studies have indicated that the effects of VPA are related to the concentration and to the exposure window, while the neurobehavioral effects of VPA have received limited research attention. In the current study, to analyze the neurobehavioral effects of VPA, zebrafish at 24 hours post-fertilization (hpf) were treated with early chronic exposure to 20 μM VPA for 7 hours per day for 6 days or with early acute exposure to 100 μM VPA for 7 hours. A battery of behavioral screenings was conducted at 1 month of age to investigate social preference, locomotor activity, anxiety and behavioral response to light change. A social preference deficit was only observed in animals with chronic VPA exposure. Acute VPA exposure induced a change in the locomotor activity, while chronic VPA exposure did not affect locomotor activity. Neither exposure procedure influenced anxiety or the behavioral response to light change. These results suggested that VPA has the potential to affect some behaviors in zebrafish, such as social behavior and the locomotor activity, and that the effects were closely related to the concentration and the exposure window. Additionally, social preference seemed to be independent from other simple behaviors.